A Type 2b von Willebrand Disease Mutation (lle546→Val) Associated with an Unusual Phenotype - Federici, A B; Mannucci, P M; Stabile, F; Canciani, M T; Di Rocco, N; Miyata, S; Ware, J; Ruggeri, Z M (Thrombosis and Haemostasis, 1997)
Type 2B von Willebrand disease (vWD) is typically characterized by enhanced ristocetin-induced platelet aggregation (RIPA) caused by increased von Willebrand factor (vWF) affinity for platelets. Furthermore, absence of larger vWF multimers in plasma is characteristic of the originally described type IIB patients, now considered a subgroup of type 2B. We describe here three affected members of a family presenting with prolonged bleeding time, thrombocytopenia, markedly enhanced RIPA and spontaneous platelet aggregation, but normal plasma vWF antigen and ristocetin cofactor activity. Larger plasma vWF multimers, albeit decreased, were present in relatively greater proportion than in other type IIB patients. Genetic studies performed in two of these patients resulted in the identification of a previously unreported A→G transition at nucleotide 4175 in the sequence of the pre-pro-vWF cDNA, corresponding to the substitution Ile546→Val in the mature vWF subunit. This mutation appears to be responsible for an unusual type 2B phenotype, with greater enhancement of the vWF platelet interaction than in typical cases but partial preservation of the larger vWF multimers in plasma.